Some kind of relative clause - Mendia, Jon Ander (Proceedings of Sinn und Bedeutung, 2019)
Amount Relatives (ARs) differ from restrictive relative clauses in that they do not refer to a particular object denoted by the head of the relative clause, but to an amount of such objects (Carlson, 1977a; Heim, 1987). Traditionally, ARs have been regarded as degree expressions. In this paper I argue against this view and propose instead that amount interpretations of relative clauses are in fact a special case of kind interpretation.